2015
DOI: 10.1111/jifm.12044
|View full text |Cite
|
Sign up to set email alerts
|

Does Short Selling Enhance the Allocational Role of Stock Price? Evidence from Hong Kong

Abstract: We investigate the real effect of short selling on corporate investments and, in particular, examine whether short selling improves managerial learning from stock prices in making investment decisions. We find that short selling improves investment sensitivity to stock price, most likely through a channel that short selling increases stock price informativeness. Using the lifting of uptick rule for index arbitrageurs and market makers as an exogenous shock to short selling intensity, we confirm the causal effe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 42 publications
0
3
1
Order By: Relevance
“…Hence, the third null sub-hypothesis is accepted; indicating that the activation of short-selling would not affect informativeness. This is inconsistent with Engelberg et al (2012), Chang et al (2014), Jiang and Pang (2016), Blau and Whitby (2018). Besides, Liq 1 has a significant positive relationship with informativeness at 0.01 level.…”
Section: Mennah Mortada Mahfouz and Nesma Ahmed Elshayebcontrasting
confidence: 75%
See 2 more Smart Citations
“…Hence, the third null sub-hypothesis is accepted; indicating that the activation of short-selling would not affect informativeness. This is inconsistent with Engelberg et al (2012), Chang et al (2014), Jiang and Pang (2016), Blau and Whitby (2018). Besides, Liq 1 has a significant positive relationship with informativeness at 0.01 level.…”
Section: Mennah Mortada Mahfouz and Nesma Ahmed Elshayebcontrasting
confidence: 75%
“…Further, Chen et al (2016) conclude that stock prices' information efficiency has a positive association with short-selling intensity. Jiang and Pang (2016) found that short-selling improves investment decisions through increasing stock price informativeness. Jin et al (2018) indicated that short-selling facilitates the flow of unfavorable news into stock prices that would improve stock price discovery and information efficiency.…”
Section: Scientific Journal For Financial and Commercial Studies And Researches (Sjfcsr) Faculty Of Commerce -Damietta Universitymentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, this study contributes to the understanding of the investment value of going concern announcements, which is shown in the market measure of both ordinary investors (momentum) and sophisticated investors (short selling volume). It also points out that the market and especially sophisticated investors (short sellers) are likely to predict upcoming negative corporate news based on both the material information contained in financial reports and market indicators (Jiang and Pang, 2016;Meng, Li, Jiang and Chan, 2017;Cheung, Hung, Lam, and Leung, 2018. ) The next section describes our sample and methodology in examining the market's ability in predicting the going concern opinion release and possible channels.…”
Section: Introductionmentioning
confidence: 99%